Maternal employment and adolescent development - Christopher J. Ruhm (Institute for the Study of Labor (IZA), 2005)
This study investigates how maternal employment is related to the outcomes of 10 and 11 year olds, controlling for a wide variety of child, mother and family characteristics. The results suggest that limited amounts of work by mothers benefit youths who are relatively disadvantaged and even long hours, which occur relatively rarely, are unlikely to leave them much worse off. By contrast, maternal labor supply is estimated to have much more harmful effects on advantaged adolescents. Particularly striking are the reductions in cognitive test scores and increases in excess body weight predicted by even moderate amounts of employment. The negative cognitive effects occur partly because maternal labor supply reduces the time these children spend in enriching home environments. Some of the growth in obesity may be related to determinants of excess weight that are common to the child and mother. Work hours are also associated with relatively large (in percentage terms) increases in early substance use and small decreases in behavior problems; however, neither are statistically significant.
Keywords: I20; J13; J18; J22; 330; maternal employment; adolescent development; child obesity; socioeconomic status; Frauenerwerbstätigkeit; Mütter; Kinder; Kognition; Verhalten; Schätzung; USA